2018
DOI: 10.14786/flr.v6i3.372
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Exploration of Two Teachers with Contrasting Emotions: Intra-Individual Process Analyses of Physiology and Interpersonal Behavior

Abstract: Although the association between teacher-student relations, teacher emotions, and burnout has been proven on a general level, we do not know the exact processes underlying these associations. Recently there has been a call for intra-individual process measures that assess what happens from moment-to-moment in class in order to better understand inter-individual differences in emotions and burnout between teachers. This paper explored the use of process measures of teachers' heart rate and their interpersonal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 113 publications
1
17
1
Order By: Relevance
“…It might be worthwhile for teacher training and professional development programs for teachers to develop a training program focused on practicing cognitive reappraisal. Recent studies in other fields have shown positive effects of such trainings on well-being and stress reduction (Denny and Ochsner, 2014;Ranney et al, 2017). In contrast to findings from other studies (mainly outside the educational context), we did not find a significant positive relationship between expressive suppression and emotional exhaustion.…”
Section: Emotion Regulation Strategies and Emotional Exhaustioncontrasting
confidence: 99%
See 2 more Smart Citations
“…It might be worthwhile for teacher training and professional development programs for teachers to develop a training program focused on practicing cognitive reappraisal. Recent studies in other fields have shown positive effects of such trainings on well-being and stress reduction (Denny and Ochsner, 2014;Ranney et al, 2017). In contrast to findings from other studies (mainly outside the educational context), we did not find a significant positive relationship between expressive suppression and emotional exhaustion.…”
Section: Emotion Regulation Strategies and Emotional Exhaustioncontrasting
confidence: 99%
“…Other aspects of teacher burnout-such as depersonalization or personal accomplishment-should be investigated to see if their association with emotion regulation differs from the findings with regard to emotional exhaustion. Also, future studies could integrate more diverse implicit measures of emotion regulation, such as physiological measures (e.g., Donker et al, 2018) or student ratings of teachers' emotion regulation (e.g., Jiang et al, 2016) to get a more integrative view of implicit processes in teachers' emotion regulation.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of social appreciation due to problematic teacher-student relationships (Donker et al 2018;Grimm 1993;Kaerner 2015;Seiboth 2015;Seifried 2009;Seifried and Sembill 2005;Sembill 1987Sembill , 2004Wulk 1988) 7…”
Section: Literature Review On Teachers' Situational Classroom Demandsmentioning
confidence: 99%
“…Thus, future studies should use video-based observations of what is going on in the classroom and use established coding systems such as the "Instrument to Identify Regulation Hindrances in Industrial Work" (RHIA) to identify regulation barriers and capacity-overtaxing factors in classroom teaching (Meder et al 2008). Combining information about "objective" situational context conditions with information on self-reports along with physiological measures (e.g., Kaerner and Koegler 2016;Kaerner et al 2017) seems to be fruitful and would give us better insights about teachers' stress in the classroom (for a good methodological example, see Donker et al 2018).…”
Section: Limitations Of the Studymentioning
confidence: 99%